IMPLEMENTASI PERATURAN BUPATI MADIUN NOMOR 39 TAHUN 2020 TENTANG PENERAPAN DISIPLIN DAN PENEGAKKAN HUKUM PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN CORONA VIRUS DISEASE 2019 DI KABUPATEN MADIUN - Sarjiyati Sarjiyati (Universitas Merdeka Madiun, 2021)
Abstract The purpose of this study was to determine the implementation of Madiun Regent Regulation Number 39 of 2020 concerning the Implementation of Health Protocol Law Enforcement as Efforts to Prevent and Control Corona Virus Disease 2019 in Madiun Regency as well as supporting and inhibiting factors in implementing the Discipline and Law Enforcement of Health Protocols as Prevention Efforts and Corona Virus Control in Madiun Regency. In this research method, researchers use empirical, namely data obtained directly through field research with primary data sources, secondary data sources and tertiary data sources as well as data collection techniques carried out by observation, interviews, document study, to informants using descriptive data analysis techniques. qualitative. The results of this study indicate that the Regent's Regulation Number 39 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control Corona Virus Disease 2019 in Madiun Regency has been implemented quite well by the Regional Government by conducting socialization related to the application of discipline and enforcement of health protocol laws. . In implementing the Regent Regulation, there are supporting and inhibiting factors. The supporting factors are agencies that play an active role in the prevention and control of the corana virus, while the inhibiting factor is the lack of public awareness to comply with health protocols, the existence of false news (hoaxes). Keywords: Implementation, Regional Regulations, Corona Virus Disease 2019, Discipline Implementation and Health Protocol Law Enforcement